Global Threat of Carbapenem-Resistant Gram-Negative Bacteria - Jean, Shio-Shin; Harnod, Dorji; Hsueh, Po-Ren (Frontiers in Cellular and Infection Microbiology, 2022)
Infections caused by multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacteria (GNB), including carbapenem-resistant (CR) Enterobacterales (CRE; harboring mainly blaKPC, blaNDM, and blaOXA-48-like genes), CR- or MDR/XDR-Pseudomonas aeruginosa (production of VIM, IMP, or NDM carbapenemases combined with porin alteration), and Acinetobacter baumannii complex (producing mainly OXA-23, OXA-58-like carbapenemases), have gradually worsened and become a major challenge to public health because of limited antibiotic choice and high case-fatality rates. Diverse MDR/XDR-GNB isolates have been predominantly cultured from inpatients and hospital equipment/settings, but CRE has also been identified in community settings and long-term care facilities. Several CRE outbreaks cost hospitals and healthcare institutions huge economic burdens for disinfection and containment of their disseminations. Parenteral polymyxin B/E has been observed to have a poor pharmacokinetic profile for the treatment of CR- and XDR-GNB. It has been determined that tigecycline is suitable for the treatment of bloodstream infections owing to GNB, with a minimum inhibitory concentration of < 0.5 mg/L. Ceftazidime-avibactam is a last-resort antibiotic against GNB of Ambler class A/C/D enzyme-producers and a majority of CR-P. aeruginosa isolates. Furthermore, ceftolozane-tazobactam is shown to exhibit excellent in vitro activity against CR- and XDR-P. aeruginosa isolates. Several pharmaceuticals have devoted to exploring novel antibiotics to combat these troublesome XDR-GNBs. Nevertheless, only few antibiotics are shown to be effective in vitro against CR/XDR-A. baumannii complex isolates. In this era of antibiotic pipelines, strict implementation of antibiotic stewardship is as important as in-time isolation cohorts in limiting the spread of CR/XDR-GNB and alleviating the worsening trends of resistance.